Social education as a factor of personality formation in the learning process - Khudaybergenova, Zilola (GeSec : Revista de Gestão e Secretariado, 2023)
The social formation of personality is a continuous natural process. Many social problems of a person and the ability to independently solve them are mainly determined by his social development. This article deals with such issues as the socialization of the individual, social education. Basic concepts and terms related to social education are interpreted. The content of social education is studied - a set of elements of social experience, which is transmitted to the younger generation in the process of social education, as well as a complex of socially significant qualities formed in young people. It describes the features of the subjects of social education - agents of positive socialization of the younger generation (and a particular child), creating conditions for the formation of a social subject. The approach of Anatoly Viktorovich Mudrik is mainly analyzed. The scientist took up this issue in the 70s. An approach to the definition of periods, mechanisms, factors of socialization, as well as the concept of "victims of socialization" is being explored. The novelty and modernity of the author's concept on this issue are put forward. The features and content of the concept of "subculture" are also considered.